Village and Small Industries Sector Framework Policy Issues and Perspective - Planning Commission (Planning Commission, 1988)
A variegated structure consisting of industrial units with different sizes, technology and organisational mode has been an essential feature of the Indian industrial scene. Even with the emergence and rapid growth of the modem large scale industries, the small, traditional and decentralised industries continue to play very important role in the economy. While part of he reason for the sustenance of the importance of this sector lies in the fact that the large scale modem industry has not been able to absorb workers to an extent good enough to effect a shift from the traditional and small sector; a more important reason for this phenomenon lies in the emphasis laid on co-existence of different sectors and promotion of small and village industries in the industrial policy followed in the post-independent India.
Planning Commission Government of India
Planning Commission Government of India